Exercise and prostate cancer: From basic science to clinical applications. Issue 9 (23rd March 2018) - Campos, Christian; Sotomayor, Paula; Jerez, Daniel; González, Javier; Schmidt, Camila B.; Schmidt, Katharina; Banzer, Winfried; Godoy, Alejandro S.
Abstract : Prostate cancer (PCa) is a disease of increasing medical significance worldwide. In developed countries, PCa is the most common non‐skin cancer in men, and one of the leading causes of cancer‐related deaths. Exercise is one of the environmental factors that have been shown to influence cancer risk. Moreover, systemic reviews and meta‐analysis have suggested that total physical activity is related to a decrease in the risk of developing PCa. In addition, epidemiological studies have shown that exercise, after diagnosis, has benefits regarding PCa development, and positive outcome in patients under treatment. The standard treatment for locally advanced or metastatic PCa is Androgen deprivation therapy (ADT). ADT produces diverse side effects, including loss of libido, changes in body composition (increase abdominal fat), and reduced muscle mass, and muscle tone. Analysis of numerous research publications showed that aerobic and/or resistance training improve patient's physical condition, such us, cardiorespiratory fitness, muscle strength, physical function, body composition, and fatigue. Therefore, exercise might counteract several ADT treatment‐induced side effects. In addition of the aforementioned benefits, epidemiological, and in vitro studies have shown that exercise might decrease PCa development. Thus, physical activity might attenuate the risk of PCa and supervised exercise intervention might improve deleterious effects of cancer treatment, such as ADT side effects. This review article provides evidence indicating that exercise could complement, and potentiate, the current standard treatments for advanced PCa, probably by creating an unfavorable microenvironment that can negatively affect tumor development, and progression.